The Influence of Customer Experience and Customer Relationship Marketing on Customer Loyalty at Jakarta Motor Tarailu, Mamuju Regency - Asri Asri; Muh Tahir; Kurnia Kurnia; Agus Halim; J. Fuji Inzani SL (Economics and Digital Business Review, 2026)
This study aims to analyze the influence of Customer Experience and Customer Relationship Marketing on Customer Loyalty at Jakarta Motor Tarailu, Mamuju Regency, both partially and simultaneously. The research employs a quantitative approach with an associative design. The sample was determined using the Lemeshow formula and the convenience sampling technique, involving 100 customers as respondents. Data were collected through observation, interviews, documentation, and questionnaires measured on a five-point Likert scale. Data analysis included validity and reliability tests, multiple linear regression, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R²), processed with IBM SPSS. The results indicate that Customer Experience has a positive and significant partial effect on Customer Loyalty (t = 5.689 > 1.985; sig. 0.000 < 0.05), and Customer Relationship Marketing also has a positive and significant partial effect on Customer Loyalty (t = 4.784 > 1.985; sig. 0.000 < 0.05). Simultaneously, both variables have a significant effect on Customer Loyalty (F = 47.152 > 3.090; sig. 0.000 < 0.05) with a coefficient of determination of 0.493, meaning that Customer Experience and Customer Relationship Marketing explain 49.3% of the variation in Customer Loyalty, while the remaining 50.7% is explained by factors outside the research model. Customer Experience is the more dominant determinant